Distributions of Xenopus species and their helminth parasites in ecological zones of Nigeria - Emmanuela U. Anele; Ishaya Haruna Nock; Ibrahim M. K. Gadzama; Grace S. N. Kia; Tharindu Premachandra; Joseph A. Jackson; Richard C. Tinsley; Ben J. Evans (PLoS ONE, 2026)
African clawed frogs ( Xenopus species) are distributed across sub-Saharan Africa, live in water, and are hosts to diverse parasites whose distributions and host-specificities are incompletely characterized. To better understand this host/parasite biodiversity, we used morphology and Sanger sequencing to characterize Xenopus species and their helminth parasites in several ecological zones of Nigeria. Five Xenopus species were identified in Nigeria ( X. fraseri , X. fischbergi , X. poweri , X. tropicalis , and X. calcaratus ), and one – Xenopus fraseri – was found to have a wide ecological tolerance in four different savanna ecological zones. Thirteen species of helminths from two phyla and five major lineages were isolated: camallanoid and seuratoid nematodes (roundworms), and cestode, digenean, and monogenean platyhelminths (flatworms). Based on our sample, the nematodes exhibited higher host generalism than the platyhelminths by infecting several host species and occurring in a wider breadth of ecological zones. In this study, all parasite species specialized either to a specific tissue (e.g., the bladder or pericardium) or a similar pair of tissues (e.g., esophagus and stomach or the lower intestine and rectum), which underscores the distinctiveness if different tissue ecosystems within a host. This study provides novel and molecularly confirmed insights into host and parasite species diversity, distributions, and ecological specificities in several ecological zones of Nigeria. Future efforts should focus on transition zones between ecological zones in Nigeria.